An Efficient Herbal Approach for Treating Fungal Infection in Cervical Cancer Patients by Developing and Optimizing a Vaginal Suppository. (5th November 2021) - Ghazwani, Mohammed; Hani, Umme; Osmani, Riyaz Ali M.; Rahamathulla, Mohamed; Begum, M. Yasmin; Wahab, Shadma; Gowda, D. V.; Ravikumar, Akhila Akkihebbal; kumar, Honnavalli Yogish; Ather, Hissana; Moin, Afrasim
Abstract : Aim . The study is aimed at developing curcumin suppositories as a promising approach for natural antifungal management of vaginal candidiasis in cervical cancer patients to eradicate side effects produced by current antifungal drugs. The objective of the study was to optimize the suppositories using optimal (custom) design employing Design-Expert 13 software to recognize the concentration of polyethylene glycols (PEG) and Poloxamer 407 and obtain a stable suppository. Methodology . Combinations of PEG 1500 (10%–40%), PEG 6000 (40%–60%), and Poloxamer 407 (5%–30%) were entered as factors, and the responses evaluated were hardness, deformation time, and % drug release. In addition, the formulation was also evaluated for visual examination, weight variation, pH determination, drug content, hardness test, disintegration time, melting zone, deformation time, in vitro drug release, antifungal activity, and stability tests. Results . Suppositories were devoid of holes and cracks, with a characteristic odor and a dark yellowish-orange color. All formulations passed the weight variation test. Formulations exhibited pH ranging from 5.5 to 6.5. Drug content was observed to be 98.65 ± 0.041 % –99.85 ± 0.041 % . The hardness of the formulation was between 2.9 and 4.2 kg/cm 2 . The disintegration time ranged from 11 ± 0.052 min to 20 ± 0.011 min . The melting point was between 41 ± 0 . 31 ° C and 58 ± 0 . 62 ° C . Deformation time ranged from 10 ± 0.45 to 35 ± 0.52 min . Most of the formulations resulted in 90% of drug release at 40 min, and the zone of inhibition noted was 19.6 ± 0.4 mm . All the selected factors have a significant effect on the response chosen for the study. Conclusion . The optimized curcumin vaginal suppository formulation can be an efficient herbal treatment devoid of side effects to treat vaginal candidiasis in cervical cancer patients.